2003
DOI: 10.1364/oe.11.003622
|View full text |Cite
|
Sign up to set email alerts
|

Effects of active fiber length on the tunability of erbium-doped fiber ring lasers

Abstract: Abstract:We numerically investigate the effects of the active fiber length on the tunability of erbium-doped fiber ring lasers for the cases of with and without pair-induced quenching (PIQ). The numerical results are confirmed by experiments. We have found that the tuning range shifts from C-band to L-band with an increase in the active fiber length. A maximum tuning range of over 100 nm, covering both the C-and L-band, can be achieved with an optimized active fiber length. It is also found that the PIQ is fav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Also, the wide bandwidth of the NPR-induced filter is in favor of realizing wide optical spectrum pulse which is favorable for short pulse duration generation. In our experiment, it is supposed that the spectral-tuning range is limited by the effective gain bandwidth provide by EDF [18,25,26]. It is expected that the broader wavelength-tunable range can be realized if other gain fiber with appropriate length and wider effective gain bandwidth is employed in the cavity such as Er-Yb co-doped fiber [42] and Tm-doped fiber [43].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Also, the wide bandwidth of the NPR-induced filter is in favor of realizing wide optical spectrum pulse which is favorable for short pulse duration generation. In our experiment, it is supposed that the spectral-tuning range is limited by the effective gain bandwidth provide by EDF [18,25,26]. It is expected that the broader wavelength-tunable range can be realized if other gain fiber with appropriate length and wider effective gain bandwidth is employed in the cavity such as Er-Yb co-doped fiber [42] and Tm-doped fiber [43].…”
Section: Resultsmentioning
confidence: 97%
“…Nevertheless, such excessively long EDF not only increases the cost, but also makes the excessive cavity length, resulting in instability and complexity of the laser. Furthermore, some studies have demonstrated that the laser wavelength-tuning range shows great dependency on the length of EDF [25,26]. Thus, in order to achieve stable and widely wavelength-tunable operation in a fiber laser, it is of particular necessary to optimize the properties of EDF.…”
Section: Introductionmentioning
confidence: 99%
“…It has been known that the emission wavelength of lasers depends on the linear cavity loss, fiber length and dopant concentration [20,21]. Sanchez's group reported the mode-locking operation at 1.6 μm in an Er-doped fiber laser by controlling the linear cavity loss [18].…”
Section: Introductionmentioning
confidence: 99%
“…In erbium-doped fiber lasers, theoretical and experimental approaches indicate that the emission wavelength depends on the cavity losses or on the active fiber length and dopant concentration [21]. Although erbium-doped fiber amplifier (EDFA) itself has a very low-gain at L-band, L-band operation have been realized in fiber lasers implement low cavity loss [22][23][24], a long length of erbium-doped fiber [25,26] and higher erbium concentration [27]. Then L-band mode locked fiber lasers have attracted much attention in recent years [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%